Teachers’ perceptions on the use of models in the teaching and learning of Geography in Gweru Urban High Schools. - Manyati, Lazmos T. (Midlands State University, 2017)
The study sought to establish teachers’ perceptions on the use of Geographical models in the teaching and learning of Geography in Gweru urban high schools. The study adopted the descriptive survey design which enabled the researcher to collect data through the use of personally distributed questionnaires, personal interviews and observation. The design helped the researcher to elicit valuable knowledge about opinions, attitudes and viewson the use of models in teaching Geography. The sample was made up of thirteen teachers,six school administrators, forty-eight students and one Geography Inspector. Data gathered was presented in tables and pie-charts. Thematic and comparative analysis followed the presentation of data. Challenges included shortage of models, time constraints, large classesand shortage of accompanying accessories like computer packages with geographical models. The results of the study paint a gloomy picture on model use in the teaching and learning of Geography. The research recommends that school administrators have to staff develop and in-service their teachers regularly on the use of models in teaching Geography. More so, there is need for the Ministry of Primary and Secondary Education to redesign the syllabus. Lastly, there is need for the government and the corporate world to assist and provide internet connections at lower rates that are affordable to schools so that models can be fully used in schools.